Organically modified hydrotalcite for compounding and spinning of polyethylene nanocomposites - L. Fambri; I. Dabrowska; A. Pegoretti; G. Ferrara (eXPRESS Polymer Letters, 2013)
Organically modified hydrotalcite is a recent class of organoclay based on layered double hydroxides (LDH), which is anionically modified with environmental friendly ligands such as fatty acids. In this paper the influence of hydrotalcite compounded/dispersed by means of two different processes for production of plates and fibers of polyolefin nanocomposites will be compared. A polyethylene matrix, suitable for fiber production, was firstly compounded with various amounts of hydrotalcite in the range of 0.5–5% by weight, and then compression moulded in plates whose thermomechanical properties were evaluated. Similar compositions were processed by using a co-rotating twin screw extruder in order to directly produce melt-spun fibers. The incorporation of clay into both bulk and fiber nanocomposites enhanced the thermal stability and induced heterogeneous nucleation of polyethylene crystals. Hydrotalcite manifested a satisfactory dispersion into the polymer matrix, and hence positively affected the mechanical properties in term of an increase of both Young’s modulus and tensile strength. Tenacity of nanocomposite as spun fibers was increased up to 30% with respect to the neat polymer. Moreover, the addition of LDH filler induced an increase of the tensile modulus of drawn fibers from 5.0 GPa (neat HDPE) up to 5.6–5.8 GPa.